2020
DOI: 10.3892/mco.2020.2026
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells and breast cancer‑specific mutations in primary breast cancer

Abstract: Circulating tumor cells (CTCs) play a pivotal role in tumor dissemination and progression, and are considered to be a critical part of the metastatic cascade. The aim of the present research article was to examine breast cancer-specific mutations in primary breast cancer (PBC) using targeted resequencing. A total of 78 patients with PBC were enrolled into this translational study. Reverse transcription-quantitative PCR assay for the expression of epithelial markers (CK19) or epithelial-to-mesenchymal transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The main cause of death among BC patients is metastasis, where circulating tumor cells (CTCs) play a crucial role [ 2 ]. In fact, CTCs’ detection and enumeration have been reported in early as well as in metastatic BC and have been associated with poor clinical outcome (decreased PFS and OS) [ 3 , 4 ]. Epithelial markers, such as EpCAM or cytokeratins (CKs), have been widely used for the characterization of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of death among BC patients is metastasis, where circulating tumor cells (CTCs) play a crucial role [ 2 ]. In fact, CTCs’ detection and enumeration have been reported in early as well as in metastatic BC and have been associated with poor clinical outcome (decreased PFS and OS) [ 3 , 4 ]. Epithelial markers, such as EpCAM or cytokeratins (CKs), have been widely used for the characterization of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, secretion of cathepsins by breast cancer cells has been shown to regulate neutrophils, enabling formation of metastatic niches in the lung [ 26 ]. EMT as well as modification of the extracellular matrix and peritumoral milieu have also been reported to be associated with increased tumor cell dissemination in breast cancer [ 27 , 28 ]. These findings may offer a molecular explanation for the association between high RS values and tumor cell dissemination into the BM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that potential diagnostic biomarkers representing stemness [ 20 ], immunogenic CTC [ 18 ], and signaling molecules that promote breast cancer metastasis [ 19 ] are found in CTCs. The mutation and expression levels of breast cancer-associated genes such as BRCA 1/2 are also detectable by liquid biopsy [ 15 , 21 ].…”
Section: Breast Cancer and Circulating Tumor Cellsmentioning
confidence: 99%